Study of the effects of spray drying in whey-starch on the probiotic capacity of Lactobacillus rhamnosus 64 in the gut of mice - Lavari, Luisina (2017)
Aims: To evaluate the effects of spray drying of Lactobacillus rhamnosus 64 on its capacity to modulate the gut immune response and on the attenuation of TNBS-induced colitis in mice. Methods and Results: Lactobacillus rhamnosus 64 was spray dried in cheese whey-starch solution and administered to mice for 3, 6 or 10 consecutive days. Peritoneal macrophage phagocytic activity, secretory IgA levels in the small intestinal fluid and TNFα, IFNγ, IL-10, IL-6 and IL-2 levels in homogenates of the small and large intestine were determined. The effects of spray drying were also evaluated in an acute model of Trinitrobenzenesulfonic acid (TNBS)-induced colitis. A shift in the regulation of immune parameters, particularly the cytokine profile, was observed for mice treated with the spray-dried culture, compared to the profile observed in animals that received the strain as fresh culture (FC). The spray-dried culture of L. rhamnosus 64 showed anti-inflammatory properties in murine model of TNBS-induced colitis. Conclusions: The spray-drying process of L. rhamnosus 64 in whey-starch modified its immunomodulating capacity in healthy animals and conferred enhanced protection in an in vivo model of inflammation. Significance and Impact of the Study: Probiotic capacity can be affected by spray drying in relation to the properties observed for the strain as an overnight FC. This fact should be taken into account when producing the culture for its application in the industry.